KERAGAMAN ALEL GADUNG LIAR (Dioscorea bulbifera L.) DI SUMATERA BARAT - Maideliza, Tesri; Mansyurdin, Mansyurdin (Makara Journal of Science, 2007)
The variety of six enzymes locus on three populations of Dioscorea bulbifera was revealed using both starch and polyacrilamide gel electrophoresis. Present study showed three polymorphic loci has each 2 alleles with nine total numbers of alleles for all populations examined. The higher alleles variety detected within population (Hs=0,08) than among population (Dst=0,04). The high levels of gene flow (0.53) were due to low differentiation among population. This result supported low levels genetic variation among population examined. Alozime data revealed moderate differentiation genetically between Western and Eastern part population from Bukit Barisan edge.